2020
DOI: 10.2967/jnumed.120.255547
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the First NRG Oncology–National Cancer Institute Workshop on Dosimetry of Systemic Radiopharmaceutical Therapy

Abstract: In 2018, the National Cancer Institute (NCI) and the NRG Oncology partnered for the first time to host a joint Workshop on Systemic Radiopharmaceutical Therapy (RPT) to specifically address issues and strategies of dosimetry for future clinical trials. The workshop focused on (1) current dosimetric approaches for clinical trials, (2) strategies under development that would provide optimal dose reporting, and (3) future desired/optimized approaches for the new and novel emerging radionuclides and carriers in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…At present, one of issues in systemic radiopharmaceutical therapy or TAT is optimizing imaging time points [2]. The previous work of Madsen et al [3] revealed a single-time to estimate the total integrated activity and absorbed dose to within 10% accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, one of issues in systemic radiopharmaceutical therapy or TAT is optimizing imaging time points [2]. The previous work of Madsen et al [3] revealed a single-time to estimate the total integrated activity and absorbed dose to within 10% accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Tb1 and Tb2 are the corresponding HL times (sec) for fast and slow biological clearances, respectively. Or, in the case of adrenals and tumor tissue, the following one-compartment equation was used: ( ) = 0 (− (2) ) { (−…”
Section: New Formalism Of Rap Methods At Time Tmentioning
confidence: 99%
“…This has been compounded by there being no recommendation, until recently, to tailor the amount of administered radioactivity in MRT treatments to individual patients. This has been partly remedied through the implementation of international directives recommending that MRT be individually planned, and its delivery verified, usually through single-photon emission computed tomography (SPECT) or positron emission tomography (PET) imaging [8,9]. In this review, MRT is defined as the use of systemically or regionally administered radiopharmaceuticals that incorporate b-electron-, a-particle-or Auger electron-emitting radionuclides for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…These workshops built upon prior workshops and symposia focused on RPT and TAT led by individual efforts by or collaborations between Department of Energy (DOE), various NIH institutes, National Academy of Sciences, and/or SNMMI [8][9][10]. More recently, the NCI-SNMMI workshops provided a forum for stakeholders representing different disciplines in academia, industry, and the government agencies to discuss not only the advances, but also the challenges of RPT and how to address them [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Robust evidence in support of this concept is necessary, which requires multidisciplinary collaboration. The NCI brought together experts in the elds of nuclear medicine, radiation oncology, and medical physics for a workshop in 2018 to address issues and strategies of dosimetry for future clinical trials [11]. This meeting resulted in several publications [15][16][17] and creation of the NCI IROC Focus Group to provide support for RPT dosimetry methodology and expertise for principal investigators of NCI-funded RPT clinical trials.…”
Section: Introductionmentioning
confidence: 99%